Synthesis, spectral characterization, thermo-kinetic and biological studies of some complexes derived from tridentate hydrazone Schiff base - Gajanan Dongare; Anand Aswar (Journal of Saudi Chemical Society)
New Schiff base hydrazone ligand 2-hydroxybenzylidene-4-oxopiperidine-1-carbohydrazone (H2L) was designed and synthesized by the condensation of 4-oxo-1-carbopiperidone hydrazide with 2-hydroxy benzaldehyde. This ligand reacts with chloride salts of Cr(III), Mn(II), Fe(III), Co(II), Ni(II) and Cu(II) to give complexes [Cr(L)(H2O)2Cl] (1), [Mn(HL)(H2O)2Cl] (2), [Fe(L)(H2O)2Cl] (3), [Co(HL)(H2O)2Cl] (4), [Ni(HL)(H2O)2Cl], (5), and [Cu(HL)(H2O)2Cl] (6), respectively. The ligand was characterized by elemental and spectral (viz. IR, UV–vis, 1H NMR and 13C NMR, mass) analyses and complexes were additionally characterized by molar conductance, magnetic susceptibility measurements, ESR, powder XRD, SEM and TG analyses. The analytical data suggest 1:1 (M: L) stoichiometric for all the complexes. The ligand behaves as a dibasic tridentate, coordinating through the Ophenolate, Nazomethine, Oenolate donor functionality towards the Cr(III) and Fe(III) ion while it behaves as monobasic tridentate and coordinates through Ophenolate, Nazomethine, Oketonic in other complexes. Physicochemical data suggests an octahedral geometry for all complexes. SEM analysis revealed regular, uniform morphological size of ligand but varies in its complexes. ESR studies confirmed that stronger covalency character in π- bonding than σ bonding. X-ray diffraction study confirms semi crystalline nature of ligand and its metal complexes. Thermal behavior (TG/DTA) and kinetic parameters calculated by Coats- Redfern method suggest more ordered activated state in complex formation. The ligand and its complexes were screened for antibacterial activity against gram-negative bacteria (Escherichia coli and S. typhi), gram-positive bacteria (Staphylococcus aureus and Bacillus substillus) and the fungal activity against pathogens (Candida albicans and Aspergillus niger) and obtained data show that metal complexes are more potent than the parent ligand against bacterial species.